2004
DOI: 10.1016/s0002-9440(10)63112-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Human Prostate Carcinoma during Hormonal Therapy Identifies Androgen-Responsive Genes and Mechanisms of Therapy Resistance

Abstract: The androgen-signaling pathway is critical to the development and progression of prostate cancer and androgen ablation is a mainstay of therapy for this disease. We performed a genome-wide expression analysis of human prostate cancer during androgen ablation therapy to identify genes regulated by androgen and genes differentially expressed after the development of resistance. Six hundred and fifty-four of 63,175 probe sets detected significant expression changes after 3 months of treatment with goserelin and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
377
4
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(409 citation statements)
references
References 21 publications
(12 reference statements)
18
377
4
10
Order By: Relevance
“…The second cohort consisted of patients treated for prostate cancer at MSKCC and consisted of prostatic tissues obtained from therapeutic or diagnostic procedures performed as part of routine clinical management of disease, hereafter referred to as the Holzbeierlein cohort. 26 This cohort was composed of 23 primary prostate tumor samples from men who received no therapy before surgery [eight of which had subsequent biochemical recurrence (BCR)], 17 primary prostate tumor samples from men who received 3 months androgen deprivation therapy (ADT) before surgery, and nine metastatic prostate cancer samples, 3 of which had progressed after ADT (Supporting Information Table 2). Expression profiling of the samples in this cohort was carried out using Affymetrix U95 human gene arrays.…”
Section: Public Prostate Cancer Cohortsmentioning
confidence: 99%
“…The second cohort consisted of patients treated for prostate cancer at MSKCC and consisted of prostatic tissues obtained from therapeutic or diagnostic procedures performed as part of routine clinical management of disease, hereafter referred to as the Holzbeierlein cohort. 26 This cohort was composed of 23 primary prostate tumor samples from men who received no therapy before surgery [eight of which had subsequent biochemical recurrence (BCR)], 17 primary prostate tumor samples from men who received 3 months androgen deprivation therapy (ADT) before surgery, and nine metastatic prostate cancer samples, 3 of which had progressed after ADT (Supporting Information Table 2). Expression profiling of the samples in this cohort was carried out using Affymetrix U95 human gene arrays.…”
Section: Public Prostate Cancer Cohortsmentioning
confidence: 99%
“…The androgen receptor signalling pathway is critical to the development and progression of CaP and BPH (Holzbeierlein et al, 2004). The AR mediates male sexual differentiation during development, sperm production from puberty, and maintenance of normal prostate (Heinlein and Chang, 2004).…”
Section: Androgen Receptor Signalling Pathwaymentioning
confidence: 99%
“…Evidence has accumulated in recent years for each of these mechanisms, suggesting that these are not mutually exclusive and that substantial hetero geneity is present [2]. It is becoming clear, for example, that ADT causes growth arrest, but does not induce significant apoptosis in prostate cancer cells [7].…”
mentioning
confidence: 99%
“…More recent in vitro evidence had shown that a subset of prostate cancer cells that survive androgendepleted conditions express increased levels of stem cell markers and are able to repopulate the tumor, possibly through adaptive AR pathway changes [9]. These adaptive changes include AR overexpression [6,10] or gain-of-function mutations [2,4] that increase receptor sensitivity to circulating androgens. Alternatively, these mutations can also allow AR to be activated by noncanonical ligands [2], such as other steroids (e.g., progesterone) [1], or even by agents initially used as antiandrogens in the same Editorial patient (e.g., flutamide and bicalutamide).…”
mentioning
confidence: 99%